2015
DOI: 10.1111/eth.12461
|View full text |Cite
|
Sign up to set email alerts
|

Algal Turbidity Hampers Ornament Perception, but Not Expression, in a Sex‐Role‐Reversed Pipefish

Abstract: Sexual ornaments are used both in intra-and intersexual contexts, and these signals have evolved to function in the particular habitat the animal is adapted to. Habitat characteristics may, however, change rapidly due to anthropogenic effects, sometimes at rates too fast for many organisms to adaptively respond. In aquatic ecosystems, eutrophication is currently changing chemical as well as visual properties of the environment. Algae blooms increase water turbidity, and the reduction of water transparency thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
(155 reference statements)
0
9
0
1
Order By: Relevance
“…Whether individuals invest more in courtship or agonistic behaviors may depend on the relative fitness benefits associated with performing either of these socio-sexual behaviors (Fitze et al, 2008;Weir et al, 2011). Environmental characteristics can mediate these gains, for example by influencing how information is transmitted (Sundin et al, 2016;Ehlman et al, 2018) and potentially modifying the type of interactions with conspecifics (e.g., Magellan and Magurran, 2006). Certain environmental characteristics may also result in differences in locomotor behaviors, particularly when enabling or interfering with individuals' movement through the environment (e.g., Marras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Whether individuals invest more in courtship or agonistic behaviors may depend on the relative fitness benefits associated with performing either of these socio-sexual behaviors (Fitze et al, 2008;Weir et al, 2011). Environmental characteristics can mediate these gains, for example by influencing how information is transmitted (Sundin et al, 2016;Ehlman et al, 2018) and potentially modifying the type of interactions with conspecifics (e.g., Magellan and Magurran, 2006). Certain environmental characteristics may also result in differences in locomotor behaviors, particularly when enabling or interfering with individuals' movement through the environment (e.g., Marras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The possibility that small individuals are less frequently encountered or not correctly identified as potential mates under turbid conditions may, however, be more likely: random encounters should be more frequent with larger individuals, or larger individuals are more easily identified as potential partners than are small individuals under low visibility regimes. Turbidity in itself does not seem to have an effect on overall swimming activity, as shown in S. typhle (Sundin et al 2010 ) as well as in the closely related straight-nosed pipefish, Nerophis ophidion (Sundin et al 2016 ). Unfortunately, we could not assess sexual selection in females due to the mold outbreak.…”
Section: Discussionmentioning
confidence: 97%
“…The difference in the relationship between male length and number of partners in the turbid and clear treatments found here was due to small males having more partners in the clear than in the turbid treatment, again showing that mate size is not important in mate choice in clear water. Previous research has shown that turbidity relaxes sexual selection on mate size (Järvenpää and Lindström 2004 ; Sundin et al 2010 ; Sundin et al 2016 ). Since mating with a larger mate may come with fitness benefits to the offspring in this species (Berglund et al 1986a ; Ahnesjö 1992 ; Mazzi 2004 ), turbidity may lead to an enhanced reproductive success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1997 ; Järvenpää and Lindström 2004 ; Wong et al. 2007 ; Candolin and Wong 2012 ; Sundin et al. 2016 ).…”
Section: Environmental Variation Mating Behavior and Sexual Selectiunclassified